Synthesis of 2D anatase TiO2 with highly reactive facets by fluorine-free topochemical conversion of 1T-TiS2 nanosheets. Issue 26 (21st June 2022) - Zarattini, Marco; Dun, Chaochao; Isherwood, Liam H.; Felten, Alexandre; Filippi, Jonathan; Gordon, Madeleine P.; Zhang, Linfei; Kassem, Omar; Song, Xiuju; Zhang, Wenjing; Ionescu, Robert; Wittkopf, Jarrid A.; et al.
Abstract : Highly crystalline anatase TiO2 nanosheets, made by controlled oxidation of TiS2 nanosheets, expose the {001} and {100} facets, giving rise to enhancement in HER as compared to Degussa P25 TiO2 nanoparticles. No enhancement in ORR was observed. Abstract : Two-dimensional (2D) anatase titanium dioxide (TiO2 ) is expected to exhibit different properties as compared to anatase nanocrystallites, due to its highly reactive exposed facets. However, access to 2D anatase TiO2 is limited by the non-layered nature of the bulk crystal, which does not allow use of top-down chemical exfoliation. Large efforts have been dedicated to the growth of 2D anatase TiO2 with high reactive facets by bottom-up approaches, which relies on the use of harmful chemical reagents. Here, we demonstrate a novel fluorine-free strategy based on topochemical conversion of 2D 1T-TiS2 for the production of single crystalline 2D anatase TiO2, exposing the {001} facet on the top and bottom and {100} at the sides of the nanosheet. The exposure of these faces, with no additional defects or doping, gives rise to a significant activity enhancement in the hydrogen evolution reaction, as compared to commercially available Degussa P25 TiO2 nanoparticles. Because of the strong potential of TiO2 in many energy-based applications, our topochemical approach offers a low cost, green and mass scalable route for production of highly crystalline anatase TiO2 with well controlled and highly reactive exposed facets.